Pengaruh Sifat Machiavellian, Komitmen Profesional, Keseriusan Pelanggaran Terhadap Niat Melakukan Whistleblowing - Ni Wayan Rusmita (UNHI Press, 2022)
The purpose of this study was to determine the effect of Machiavellian, Professional Commitment and the Seriousness of Violations on Intentions to Whistleblowing. This research was conducted at the BPK RI Representatives of the Province of Bali. The method used is a quantitative research method. The data used in this study is primary data using a questionnaire as a method of collecting data obtained from respondents. The population in this study is the auditors who work at the BPK RI Representatives of the Province of Bali as many as 55 people. The sampling technique used in this study was non-probability sampling with a saturated sample type so that the number of samples in this study was 55 people. The analysis technique used is Multiple Linear Regression Analysis. The results of this study indicate that the influence of Machiavellian, Professional Commitment and the Seriousness of Violations has a positive and significant effect on the Intention to Whistleblowing.